2020
DOI: 10.1590/0037-8682-0714-2020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 gastrointestinal manifestations: a systematic review

Abstract: Introduction: The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has greatly challenged public health worldwide. A growing number of studies have reported gastrointestinal (GI) symptoms. We performed a systematic review of GI symptoms associated with coronavirus disease 2019 (COVID-19) as well as of the serum levels of biomarkers related to liver function and lesion in SARS-CoV-2-infected individuals. Methods: We surveyed relevant articles published in English, Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
2
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 68 publications
(84 reference statements)
0
53
2
15
Order By: Relevance
“…We also show a shallow frequency of diarrhea (0.7 %) which contrasts with data from other meta-analyses that report pooled frequencies from 11 to 19 % [ 45 , 49 , 50 ]. Additionally, we also demonstrated that patients with diarrhea had significantly lower RNA copies than patients without gastrointestinal symptoms (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…We also show a shallow frequency of diarrhea (0.7 %) which contrasts with data from other meta-analyses that report pooled frequencies from 11 to 19 % [ 45 , 49 , 50 ]. Additionally, we also demonstrated that patients with diarrhea had significantly lower RNA copies than patients without gastrointestinal symptoms (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…This hypothesis involves the downregulation of ACE2 on intestinal cells after SARS-CoV-2 binding. Reduction in the expression of ACE2 leads to decreased activation of the mechanistic target of rapamycin (mTOR) signaling cascade, which signals exacerbated inflammation, leaky gut, and increased autophagy ( Chiappini et al, 2020 ; da Silva et al, 2020 ).…”
Section: Route Of Entry and Neuroinvasive Mechanisms Of Sars-cov-2 Anmentioning
confidence: 99%
“…Additionally, COVID-19 patients also present gastrointestinal alterations (Silva et al, 2020 ). As already described in MERS-CoV infection (Zhou et al, 2017 ), a new potential route for viral neuroinvasion has been proposed for SARS-CoV-2 (Esposito et al, 2020 ).…”
Section: Potential Neuro-invasive Mechanisms Of Sars-cov-2mentioning
confidence: 99%
“…As already described in MERS-CoV infection (Zhou et al, 2017 ), a new potential route for viral neuroinvasion has been proposed for SARS-CoV-2 (Esposito et al, 2020 ). In vitro experiments, using human small intestine and brain organoids, and histological characterizations for human intestine samples, have demonstrated the capacity of SARS-CoV-2 to infect the gastrointestinal tract (Lamers et al, 2020 ; Zhang H. et al, 2020 ; Silva et al, 2020 ; Kumari et al, 2021 ). This invasion may activate the enteric glial cells inducing the cytokine storm observed in COVID-19 patients (Esposito et al, 2020 ).…”
Section: Potential Neuro-invasive Mechanisms Of Sars-cov-2mentioning
confidence: 99%